Designing an Efficient Lead-Free Perovskite Solar Cell through a Computational Method - Bhattarai, Sagar; Kalita, P. K; Hossain, Ismail; Alsubaie, Abdullah Saad; Mahmoud, Khaled Hussein; Ansari, Mohd Zahid; Janíček, Petr (MDPI, 2023)
Organometallic halide perovskite (PVK)-based solar cells (PSC) have gained significant popularity owing to their efficiency, adaptability, and versatility. However, the presence of lead in conventional PVK poses environmental risks and hinders effective commercialization. Although lead-free PVK solar cells have been developed, their conversion efficiency is limited due to intrinsic losses. To address this challenge, we present a simulation study focusing on methylammonium tin bromide (MASnBr3) as an alternative material. In our investigation, the MASnBr3 layers are strategically placed between a copper iodide (CuI)-based hole transporting material (HTM) and a zinc oxide (ZnO)-based electron transporting material (ETM). We optimize the active layer thickness, operating temperature, defect density analysis, and series resistances to assess device performance. Furthermore, we employ contour mapping, considering both thickness and defect density, for a detailed investigation. Our primary objective is to achieve unprecedented efficiency in lead-free MASnBr3-based PSCs. Remarkably, our study achieves the highest JSC (short-circuit current density) of 34.09 mA/cm2, VOC (open-circuit voltage) of 1.15 V, FF (fill factor) of 82.06%, and optimized conversion efficiency of 32.19%. These advancements in conversion efficiency pave the way for the development of lead-free PVK solar cells in the desired direction.
Návrh efektivního bezolovnatého perovskitového solárního článku pomocí výpočetní metody
Keywords: perovskite (PVK); methylammonium tin bromide (MASnBr3); hole transport material (HTM); power conversion efficiency (PCE); perovskit (PVK); methylamonium cín bromid (MASnBr3); materiál pro přenos děr (HTM); účinnost přeměny energie (PCE)